Effect of Fe(III)-ligand properties on effectiveness of modified photo-Fenton processes - Aplin, R (Water science and technology : a journal of the International Association on Water Pollution Research, 2001)
This paper examines a modified photo-Fenton (UV/Fe oxalate/H2O2) process. The degradation of oxalate in this system in the absence of Reactive Red 235 was studied using both experimentation and kinetic modelling. The degradation of Reactive Red 235 in this system was also studied. Light intensity and solution pH had large effects on the degradation of both oxalate and Reactive Red 235, with the effect of pH not due simply to speciation changes. The most important properties of the oxalate ligand in the UV/Fe oxalate/H2O2 process are that it forms Fe(III)-oxalato complexes that are easily photolysed and also is relatively unreactive with OH. radicals